Production Performance of Gracilaria verrucosa using Verticulture Method with Various Wide Planting Area in Karimunjawa - Titik Susilowati; Agus Nadlir; Alfabetian Harjuno Condro Haditomo; Seto Windarto; Dicky Harwanto; Kurnia Adi (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2019)
Gracilaria verrucosa is one type of seaweed that can be developed into a high-value product. Market demand for agar reaches 21.8% per year, but only 13.1% can be met. This is due to the low level of production of G. verrucosa in Indonesia. Utilization of G. verrucosa is still relying on aquaculture from the farm, which causes low production. Cultivation of seaweed with verticulture methods can increase the production of G. verrucosa. Karimunjawa is a potential area for seaweed cultivation. The aim of this study is to determine the effect of different density areas on the growth and production of G. Verrucosa and to determine the best density area for its production in Karimunjawa. This research used G. verrucosa wrapped in a mesh size of 0.5cm with a weight of 50g per pack. Each verticulture strap contains 4 packs and each treatment consists of 9 straps. The treatment was in the form of differences in the planting area of 25x25cm2 (A), 50x50cm2 (B) and 75x75cm2 (C). The results showed significant differences (P <0.01) between each treatment. The 75x75cm2 area has the best yield on absolute growth, relative growth rate (RGR) and specific growth rate (SGR) of 83.10 ± 4.12g; 3.96 ± 0.20% / day and 2.33 ± 0.07% / day. The best results of G. verrucosa production obtained at an area of 50x50cm2 (5.32 ± 0.26 kg / m2).